Drought-Induced Human Displacement in Turkey - Delju, Amir H. (My University, 2019)
This paper analyses the correlation between drought spells, using the Standardized Precipitation Index and internal migration in rural communities in Turkey between 2007 and 2015. It aims to assess the quantified and evidencebased relationship between the compound effect of drought and migration in Turkey. As the correlation coefficient between the SPI and the Rate of Net Migration showed direct links between drought and internal migration, we arranged the twelve statistical regions of Turkey into three groups: a) magnet for migrants, b) neutral regions, and c) sources of out-migration. Based on the review of reference materials, it appeared that economy and security were the most powerful nonclimate factors that affected migration. In our analysis, we demonstrate that the impact of drought varies across the country depending on each region’s climate pattern, socio-economic situation, security, and stability. The net impact of drought and climate variability on migration in Turkey is determining, yet not absolute. It hides behind non-climatic elements, some of which appear as strong drivers for migration. The study also revealed that in the regions where security was not an issue, wet periods coincided with a lower flow of out-migration from rural areas. Finally, we have noted that the economic diversification of Turkey presents attractive opportunities and thus affects the preferred choice of rural emigrants for internal displacement.
Keywords: Drought; Climate; Impact assessment; Agriculture; Internal migration; Turkey